Oncogene cooperation in lymphocyte transformation: malignant conversion of E mu-myc transgenic pre-B cells in vitro is enhanced by v-H-ras or v-raf but not v-abl. - Alexander, W S (1989)
Although transgenic mice bearing a c-myc gene controlled by the immunoglobulin heavy-chain enhancer (E mu) eventually develop B-lymphoid tumors, B-lineage cells from preneoplastic bone marrow express the transgene but do not grow autonomously or produce tumors in mice. To determine whether other oncogenes can cooperate with myc to transform B-lineage cells, we compared the in vitro growth and tumorigenicity of normal and E mu-myc bone marrow cells infected with retroviruses bearing the v-H-ras, v-raf, or v-abl oncogene. The v-H-ras and v-raf viruses both generated a rapid polyclonal expansion of E mu-myc pre-B bone marrow cells in liquid culture and 10- to 100-fold more pre-B lymphoid colonies than normal in soft agar. The infected transgenic cells were autonomous, cloned efficiently in agar, and grew as tumors in nude mice. While many pre-B cells from normal marrow could also be induced to proliferate by the v-raf virus, these cells required a stromal feeder layer, did not clone in agar, and were not malignant. Most normal cells stimulated to grow by v-H-ras also cloned poorly in agar, and only rare cells were tumorigenic. With the v-abl virus, no more cells were transformed from E mu-myc than normal marrow and the proportion of tumorigenic pre-B clones was not elevated. These results suggest that both v-H-ras and v-raf, but apparently not v-abl, collaborate with constitutive myc expression to promote autonomous proliferation and tumorigenicity of pre-B lymphoid cells.